An Overview of Vulture Conservation in Nepal - Thapa, Ishana (The Initiation, 2010)
Two species of vulture White-rumped Gyps bengalensis and Slender-billed G. tenuirostris are in grave danger of extinction with rapid decline throughout their ranges in Nepal with the complete loss of breeding colonies and local extinctions increasingly taking place. Nepal Government has already banned veterinary drug diclofenac which is the major cause of decline due to poisoning in food supply. Meloxicam has been widely promoted as the safe replacement of Diclofenac. Captive population have been established at Kasara, Chitwan National Park for future reintroduction. To reduce mortality in the wild in situ measures have been initiated through establishment of vulture restaurants as safe feeding sites. Key Words: Critically endangered, Diclofenac, Meloxicam, Conservation, Breeding centre, Vulture restaurant DOI: 10.3126/init.v3i0.2502 The Initiation Vol.3 2009 p.114-118